Sports injuries in children and adolescents - Karantanas, Apostolos H. (Medical Radiology, 2010)
Children and adolescents increasingly participate in competitive sports, resulting in a higher incidence of acute and overuse injuries. While some sports injuries mirror those in adults, others are unique owing to the inherent weakness of the growing skeleton at specific sites. Imaging plays an important role in the diagnosis and management of these entities, and radiologists need to be familiar with the advantages and limitations of the various imaging modalities when evaluating the injured young athlete. This book, written by leading experts from Europe and the United States, covers a wide spectrum of sports injuries seen in children and adolescents. The first part comprises a series of introductory chapters on topics such as the clinician?s viewpoint, the normal anatomy and variants, the imaging of articular cartilage, and the current role of ultrasonography in imaging injured young athletes. In subsequent chapters, each important site of injury is considered individually with the aid of informative images. The final part of the book resembles an atlas and presents the most commonly encountered injuries in the popular sports of football, skiing, water sports, tennis, and gymnastics. Throughout, particular attention is paid to the most recent advances in knowledge and imaging.